Novel triazole-tetrahydroisoquinoline hybrids as human aromatase inhibitors - Chanamon Chamduang (2020)
© 2019 Elsevier Inc. Novel thirteen triazole-tetrahydroisoquinoline derivatives (2a-m) were synthesized and evaluated for their aromatase inhibitory activities. Seven triazoles showed significant aromatase inhibitory activity (IC50 = 0.07–1.9 μM). Interestingly, the analog bearing naphthalenyloxymethyl substituent at position 4 of the triazole ring (2i) displayed the most potent aromatase inhibitory activity (IC50 = 70 nM) without significant cytotoxicity to a normal cell. Molecular docking also suggested that the direct H-bonding interaction with residue Thr310 may be responsible for a striking inhibitory effect of the most potent compound 2i.